The provision of liquidity in the Swedish note-banking system - Per Hortlund (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
The working of the asset currency provided by the Swedish note banking system in 1878-1901 is described. Natural and institutional conditions caused the demand for currency to peak in March and September, with troughs in July and January. The paper investigates how the Enskilda banks provided liquidity to solve the problem. This is done by describing how the volume of notes varied over the year, and how other balance sheet items co-moved with them. Strong seasonal co-variation is found particularly between lending and foreign payments media, varying like communicating vessels over the sailing season in May-October (when the sea was ice free and shipments were made).
Keywords: G21; N13; N23; 330; Free banking; Elastic currency; Asset currency; Clearing mechanism; Note competition; Needs of trade; Lender of last resort; Sailing season; Free Banking; Bankgeschichte; Schweden